2018
DOI: 10.5114/pjr.2018.75808
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography urography with iterative reconstruction algorithm in congenital urinary tract abnormalities in children – association of radiation dose with image quality

Abstract: PurposeTo assess the extent to which a radiation dose can be lowered without compromising image quality and diagnostic confidence in congenital urinary tract abnormalities in children by using a CT scanner with an iterative reconstruction algorithm.Material and methods120 CT urography image series were analysed retrospectively. Image series were divided into four study groups depending on effective radiation dose (group 1: 0.8-2 mSv; group 2: 2-4 mSv; group 3: 4-6 mSv; group 4: 6-11 mSv). Objective and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…First, scanning parameters were different between patients and radiation exposure assessment was not a goal of this study. However, our recent research already confirmed that there are no significant differences in subjective image quality and diagnostic confidence between lower dose and higher dose examinations [38]. Second, we did not perform objective density measurements of the collecting systems, as there were different doses of furosemide, adapted to patients' weight.…”
Section: Discussionmentioning
confidence: 96%
“…First, scanning parameters were different between patients and radiation exposure assessment was not a goal of this study. However, our recent research already confirmed that there are no significant differences in subjective image quality and diagnostic confidence between lower dose and higher dose examinations [38]. Second, we did not perform objective density measurements of the collecting systems, as there were different doses of furosemide, adapted to patients' weight.…”
Section: Discussionmentioning
confidence: 96%
“…The provision of a high radiation dose is an important issue in CTU in human medicine. Many efforts to reduce the radiation dose have been attempted, including reducing the number of imaging phases through the use of dual-energy CT, applying a split-bolus technique, changing the scanning parameters employed such as by lowering tube voltage or applying several iterative reconstruction algorithms [ 17 18 19 ]. Radiation exposure may not be as big a concern in veterinary medicine as it is in humans; however, considering the increased use of CT for assessment of the urinary tract and other organs, as well as the wide availability of multi-detector CT devices, the split CTU technique can reduce radiation exposure.…”
Section: Discussionmentioning
confidence: 99%